Pengaruh Permainan Papan Cocok Terhadap Kemampuan Mengenal Warna pada Anak Usia 4-5 Tahun di TK Negeri Pembina Ki Hajar Dewantoro Kecamatan Dungingi - Marmin Adam; Yakob Napu; Yenti Juniarti (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study aimed to determine whether there is an Effect of Matching Board Games on the Color Recognition Skills in Children Aged 4-5 Years at TK Negeri Pembina Ki Hajar Dewantoro, Dungingi Subdistrict. This study used a quantitative experimental method. The research findings involving 15 children revealed that there was an increase in the results of the Pre-test and Post-Test. In this case, it was observable from the Pre-test data obtaining an average value of 16.06 and a standard deviation of 2.604 and the Post-Test data was with an average value of 21 and a standard deviation of 3.461. in reference to these findings, the respondents who were samples in this study obtained an increase in average results from the pre-test to the post-test.